2019
DOI: 10.1111/jce.14246
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous left atrial appendage closure in the presence of thrombus: A feasibility report

Abstract: Background Patients with a left atrial appendage thrombus (LAAT) despite oral anticoagulation (OAC) are at high risk of thromboembolism (TE) and a relevant proportion of LAAT do not resolve under continued OAC. Left atrial appendage closure (LAAC) in the presence of LAAT was anecdotally described as a therapeutic option to prevent TE in the patients. Objective To describe the feasibility of LAAC despite LAAT in consecutive patients. Methods We searched the LAAC database of our center to identify patients in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 23 publications
2
13
0
1
Order By: Relevance
“…Tarantini et al [5] showed that over one-third (39.3%) of their patients on discharge received dual antiplatelet therapy, which was followed by oral anticoagulants (28%) and low-molecularweight heparin (18%), while approximately 10% had combinations of antiplatelets and oral anticoagulants prescribed. After 6 months, similarly to the observations of other authors [5,10], approximately half of the patients (45%) in our group were only on aspirin, although many (45%) still remained on oral anticoagulants. There is a general consensus to prescribe aspirin monotherapy for half a year after an LAA closure procedure in typical conditions [6].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Tarantini et al [5] showed that over one-third (39.3%) of their patients on discharge received dual antiplatelet therapy, which was followed by oral anticoagulants (28%) and low-molecularweight heparin (18%), while approximately 10% had combinations of antiplatelets and oral anticoagulants prescribed. After 6 months, similarly to the observations of other authors [5,10], approximately half of the patients (45%) in our group were only on aspirin, although many (45%) still remained on oral anticoagulants. There is a general consensus to prescribe aspirin monotherapy for half a year after an LAA closure procedure in typical conditions [6].…”
Section: Discussionsupporting
confidence: 90%
“…Some of our patients had procedures performed on an infusion of unfractionated heparin in order to maintain a small thrombus size and prevent the possible formation of clots on endovascular tools. Unfortunately, neither the Italian nor German groups [5,10] reported this important periprocedural detail. Experience gathered from catheter ablations of atrial fibrillation showed that instrumentation of the left atrium can be relatively safely performed on uninterrupted anticoagulant therapy [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations